2011
DOI: 10.1074/jbc.m110.162321
|View full text |Cite
|
Sign up to set email alerts
|

Lys-63-specific Deubiquitination of SDS3 by USP17 Regulates HDAC Activity

Abstract: SDS3 is a key component of the histone deacetylase (HDAC)-dependent Sin3A co-repressor complex, serving to maintain its HDAC activity. Here, we report both exogenous and endogenous functional interaction between deubiquitinating enzyme USP17 and human SDS3 by MALDI-TOF-MS, co-immunoprecipitation assay, and GST pull-down assay. In this study, we demonstrated that SDS3 readily undergoes endogenous polyubiquitination, which is associated specifically with Lys-63-branched polyubiquitin chains and not with Lys-48-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 41 publications
1
38
0
Order By: Relevance
“…Polyubiquitination with linkages at this residue is involved in proteasomal degradation (22). Cotransfection and immunoprecipitation of Taz with β-TrCP yielded a polyubiquitination pattern, which was diminished in the presence of active Src (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Polyubiquitination with linkages at this residue is involved in proteasomal degradation (22). Cotransfection and immunoprecipitation of Taz with β-TrCP yielded a polyubiquitination pattern, which was diminished in the presence of active Src (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…5B), indicating that FHF1 negatively regulated polyubiquitylation of NEMO. To determine if FHF1b was affecting either K48-linked (thus implicating FHF1b in the regulation of NEMO stability) or K63-linked polyubiquitylation (and hence assembly of the IKKsignalosome), we employed ubiquitin-mutant proteins in this assay, where all five lysine-residues are mutated to arginine, except residues K48 or K63 (R48K, R63K) (Ramakrishna et al, 2011), respectively. Interestingly, FHF1b co-transfection resulted in reduced R48K and R63K polyubiquitylated NEMO, indicating that, in addition to regulating NEMO activity, FHF1 may also affect NEMO stability (Fig.…”
Section: Fhf1 and Neuronal Nf-kb 6061mentioning
confidence: 99%
“…We previously generated USP17-specific antibodies and found that USP17-mediated cell proliferating mechanism is associated with histone deacetylase (HDAC) activity. (20,21) To our knowledge, previous studies have shown that USP20 participates in various cell systems, but the exact mechanisms of USP20 are not yet fully understood, and there may be other substrates for USP20. Thus, our results may help in the investigation of USP20-related cellular mechanisms by offering an opportunity to use diversely applicable USP20-specific antibodies.…”
Section: Discussionmentioning
confidence: 96%